Human embryology in the holy Qur'an : a comparative study between Tantawi Jawhari's and Zaghloul Naggar's interpretations - Mizanur Rahman, 1990- (Kulliyyah of Islamic Revealed Knowledge and Human Sciences ,International Islamic University Malaysia, 2016)
One of the most important scientific indications mentioned in the Holy Qur´an is the embryonic development of human beings in the mother's womb. The Holy Qur´an provides a detailed description of the scientific events in embryonic development, from the stages of gamete and conception until full-term pregnancy and delivery. Commentators of the Holy Qur´an have explain the issue of the early stages of human reproduction in their works differently. Some of them explained it from the scientific perspective while others regard it impermissible and interpreted the ayah from the linguistic angle. Tantawi Jawhari and Zaghloul Naggar deal with the ayat from the scientific viewpoint. They agree on some issues while maintaining differences on some others. No academic research so far has been carried out on Naggar's commentary of the Holy Qur´an. Hence, it seems significant to deal with the issue of human embryology from the scientific perspective based on the writings of the two prominent scholars. Descriptive, analytical and comparative methods have been essentially applied in this research. Descriptive method has been employed in Chapter Two, where the life and contributions of these two scholars are illustrated in detail; while analytical method has been used in Chapters Three and Four, where the concept of scientific tafsir, its development, the viewpoints of scholars and the methodology of these two scholars applied in their tafsirs have been analyzed accordingly. Lastly, Chapter Five has been devoted to comparative analysis between the views of the two scholars in their exegeses on human embryology. The research suggests that scientific interpretation of the Holy Qur´an remains permissible with certain conditions. The study also reveals that the interpretations of Zaghloul Naggar on the verses of human embryology are more precise as well as relevant to the practical science of embryology compared to the interpretation of Tantawi Jawhari. Finally, this research suggests that without proper Qur´anic knowledge and scientific insights, no one should talk about the natural phenomena and the scientific indications mentioned in the Holy Qur´an; otherwise, it may lead to misinterpretation of the holy book of Allah, revealed for the guidance of humankind.